👤

3. If a - 3 = 1, then a = 4.


Sagot :

True?

4 - 3 = 1

:DDDDDDDDD

Answer:

Addition property of equality

Step-by-step explanation:

To solve the equation a - 3 = 1, we need to isolate the variable, which is a to solve the equation.

Since we have constant term on LHS (left hand side), i.e., -3, we need to cancel it out so that we can isolate  a.

To cancel it out simply add its inverse to both sides, which is 3.

So,

a - 3 + 3 = 1 + 3

a = 4

Since we added a positive number to both sides, we used addition property of equality to solve for a.